2001
DOI: 10.1126/science.1059829
|View full text |Cite
|
Sign up to set email alerts
|

Protective Role of ATP-Sensitive Potassium Channels in Hypoxia-Induced Generalized Seizure

Abstract: Adenosine triphosphate (ATP)-sensitive potassium (K(ATP)) channels are activated by various metabolic stresses, including hypoxia. The substantia nigra pars reticulata (SNr), the area with the highest expression of K(ATP) channels in the brain, plays a pivotal role in the control of seizures. Mutant mice lacking the Kir6.2 subunit of K(ATP) channels [knockout (KO) mice] were susceptible to generalized seizures after brief hypoxia. In normal mice, SNr neuron activity was inactivated during hypoxia by the openin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
245
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 322 publications
(259 citation statements)
references
References 21 publications
10
245
0
Order By: Relevance
“…141 Because K ATP channels may be activated mainly under conditions of neuronal energy failure (they are inhibited by ATP), such as in anoxia, openers of K ATP channels are unlikely to have broad utility in epilepsy therapy, although they might in theory be useful for the treatment of anoxia-induced seizures. 142,143 K ATP channels are, however, present in peripheral tissues, including the heart and vasculature; to date, no K ATP opener has been found that does not have adverse cardiovascular effects due to actions on these peripheral channels.…”
Section: Voltage-gated Potassium Channelsmentioning
confidence: 99%
“…141 Because K ATP channels may be activated mainly under conditions of neuronal energy failure (they are inhibited by ATP), such as in anoxia, openers of K ATP channels are unlikely to have broad utility in epilepsy therapy, although they might in theory be useful for the treatment of anoxia-induced seizures. 142,143 K ATP channels are, however, present in peripheral tissues, including the heart and vasculature; to date, no K ATP opener has been found that does not have adverse cardiovascular effects due to actions on these peripheral channels.…”
Section: Voltage-gated Potassium Channelsmentioning
confidence: 99%
“…Considering CK equilibrium in the membrane vicinity (12) and the relationships between concentrations (Eq. 11) and fluxes (Eqs 2, 7 and 8), values of ΔATP, ΔADP, ΔCr and ΔCrP can be derived as Eq.…”
Section: Ck-facilitated Nucleotide Diffusion In the Compartmentalizedmentioning
confidence: 99%
“…At equilibrium, defining total bulk concentration for Cr plus CrP [CrT] = 40 mM [44], and total bulk nucleotide pool [TNP], it follows from Eq. 9: (10) At steady-state, total adenine nucleotide flux and total Cr/CrP flux, imply, due to Eqs 2 and 8, that (11) Considering CK equilibrium in the membrane vicinity (12) and the relationships between concentrations (Eq. 11) and fluxes (Eqs 2, 7 and 8), values of ΔATP, ΔADP, ΔCr and ΔCrP can be derived as Eq.…”
Section: Ck-facilitated Nucleotide Diffusion In the Compartmentalizedmentioning
confidence: 99%
See 2 more Smart Citations